Porous sound-absorbing material, and method for manufacturing a porous sound-absorbing material
Patent Information
- Application Number
- JP2025059666
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0017】 本発明によれば、低周波数側の吸音性に優れる多孔質吸音材を提供できる。 また、本発明によれば、低周波数側の吸音性に優れる多孔質吸音材の製造方法を提供できる。
Smart Images

Figure 2026166612000001
Abstract
Description
[Technical Field]
[0001] This invention relates to a porous sound-absorbing material and a method for producing a porous sound-absorbing material. [Background technology]
[0002] Sound-absorbing materials are used in various fields such as architecture, mobility, and acoustics. Generally, porous sound-absorbing materials, perforated sound-absorbing materials, and plate-type sound-absorbing materials are known, with porous sound-absorbing materials being particularly extensively developed. Specifically, glass wool and rock wool products, which are made by forming short fibers such as glass into boards, and granular cotton, which is made by shaping short fibers into granules, have been put into practical use.
[0003] In the mobility sector, particularly in automobiles, porous sound-absorbing materials are used to reduce unpleasant noise during driving and improve comfort inside the vehicle.
[0004] In recent years, the power sources of automobiles have been rapidly electrified to reduce greenhouse gas emissions. With the electrification of power sources, relatively low-frequency noises that were previously masked by engine noise (approximately 200-10,000 Hz), such as road noise (approximately 100-1,000 Hz) generated from the contact between the tires and the ground while the car is in motion, and wind noise (approximately 900-10,000 Hz) while driving, may become more apparent. Therefore, there is a need to develop porous sound-absorbing materials that can effectively absorb these noises. Furthermore, while the overall sound absorption performance of porous sound-absorbing materials can be improved by increasing their usage, this increases the vehicle's weight, leading to decreased efficiency in areas such as fuel consumption and electricity consumption, as well as reduced driving performance. Therefore, there is a need to develop lighter porous sound-absorbing materials that maintain high sound absorption performance.
[0005] Against this backdrop, for example, Patent Document 1 describes a porous sound-absorbing material that exhibits an even higher sound absorption rate in the low-frequency range than a nonwoven fabric that is lightweight and has a well-balanced sound absorption rate across a wide range from low to high frequencies. This porous sound-absorbing material contains fibers and has a density of 0.5 mg / cm³. 3 ~20 mg / cm³ 3A porous sound-absorbing material made of porous material has been proposed. [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] Japanese Patent Publication No. 2021-179459 [Overview of the project] [Problems that the invention aims to solve]
[0007] Therefore, further development of porous sound-absorbing materials with excellent sound absorption properties at low frequencies is desired.
[0008] Therefore, the present invention aims to provide a porous sound-absorbing material that exhibits excellent sound absorption on the low-frequency side. Furthermore, the present invention aims to provide a method for manufacturing a porous sound-absorbing material that exhibits excellent sound absorption on the low-frequency side. [Means for solving the problem]
[0009] The inventors diligently conducted research with the aim of solving the above problems. As a result, the inventors newly discovered that the above problems can be solved if the porous sound-absorbing material contains a porous resin and carbon nanotubes that coat the surface of the porous resin, and has a density within a predetermined range, and thus completed the present invention.
[0010] In other words, the present invention aims to advantageously solve the above problems, [1] the present invention comprises a porous resin and carbon nanotubes covering the surface of the porous resin, with a density of 0.100 g / cm³ 3 More than 0.300g / cm 3 The following is a porous sound-absorbing material. Porous sound-absorbing materials like those described above excel at absorbing low frequencies. In this specification, the density of a porous sound-absorbing material can be measured according to the method described in the examples of this specification. In the present specification, "carbon nanotubes covering the surface of the porous resin" includes not only carbon nanotubes covering the outer surface of the porous resin, but also carbon nanotubes covering the surfaces of the pores present inside the porous resin. The covering of the surface of the porous resin with carbon nanotubes may be on the entire surface of the porous resin or on a part of the porous resin.
[0011] [2] In the porous sound absorbing material according to the above [1], the average pore diameter A by the mercury intrusion method is preferably 5.0 μm or more and 35.0 μm or less. When the average pore diameter A of the porous sound absorbing material is not less than the above lower limit, any silica xerogel can be effectively accommodated in the voids (pores) of the porous resin. On the other hand, when the average pore diameter A of the porous sound absorbing material is not more than the above upper limit, the sound absorbing property on the low frequency side of the porous sound absorbing material can be effectively improved. In the present specification, the average pore diameter A by the mercury intrusion method is an average pore diameter measured by the mercury intrusion method, and can be measured according to the method described in the Examples of the present specification.
[0012] [3] In the porous sound absorbing material according to the above [1] or [2], the average pore diameter B by the BJH method is preferably 5.0 nm or more and 30.0 nm or less. When the average pore diameter B of the porous sound absorbing material is within the above range, the sound absorbing property on the low frequency side of the porous sound absorbing material can be effectively improved. In the present specification, the average pore diameter B by the BJH method is the average pore diameter of mesopores (3.4 nm to 200 nm) in the porous sound absorbing material measured by the BJH method in the nitrogen adsorption method, and can be measured according to the method described in the Examples of the present specification.
[0013] [4] The porous sound absorbing material according to any one of the above [1] to [3] preferably further comprises a silica xerogel containing the polysiloxane particles. When the porous sound absorbing material further comprises a silica xerogel containing polysiloxane particles, the sound absorbing property on the low frequency side of the porous sound absorbing material can be improved. Here, the term "xerogel" refers to, according to "Definitions of Terms Relating to Structure and Processes of Sols, Gels, Networks, and Inorganic-Organic Hybrid Materials (IUPAC Recommendations 2007)" by the Inorganic Chemistry Division and the Subcommittee on Polymer Terminology of the Macromolecular Division of the International Union of Pure and Applied Chemistry (IUPAC), "a gel composed of an open network formed by removing the swelling agent from a gel". There is also a classification system in which the product obtained by removing the swelling agent (solvent) by supercritical drying is defined as an aerogel, the product obtained by removing the swelling agent (solvent) by ordinary evaporative drying is defined as a xerogel, and the product obtained by removing the swelling agent (solvent) by freeze drying is defined as a cryogel. In the present specification, these are collectively referred to as "xerogel".
[0014] [5] In the porous sound-absorbing material according to the above [4], it is preferable that the porous resin has an interconnected pore structure, the silica xerogel has a structure in which the polysiloxane particles are connected in a pearl necklace shape, and the silica xerogel is present in the interconnected pores of the porous resin. When the porous resin and the silica xerogel each have the above structure, and the silica xerogel is present in the interconnected pores of the porous resin, the sound absorption performance on the low frequency side of the porous sound-absorbing material can be further improved. In the present specification, "pearl necklace shape" means that the polysiloxane particles are three-dimensionally connected to each other to form a shape like a pearl necklace. In the present specification, "interconnected pore structure" refers to a structure constituting a part of the porous resin, in which a plurality of fine pores are formed from the surface toward the inside of the porous sound-absorbing material, and the plurality of pores do not exist independently, but communicate with (are connected to) each other.
[0015] [6] In the porous sound-absorbing material according to the above [4] or [5], the content ratio of the polysiloxane particles in the porous sound-absorbing material is preferably 10 mass% or more and 85 mass% or less. When the content ratio of the polysiloxane particles in the porous sound-absorbing material is not less than the above lower limit, the sound absorption performance on the low frequency side of the porous sound-absorbing material can be effectively improved. On the other hand, if the proportion of polysiloxane particles in the porous sound-absorbing material is below the above upper limit, the porous sound-absorbing material can be effectively made lighter. In this specification, the proportion of polysiloxane particles in a porous sound-absorbing material can be measured according to the method described in the examples of this specification.
[0016] Furthermore, the present invention aims to advantageously solve the above problems, [6] and the present invention is a method for producing a porous sound-absorbing material, comprising: a homogeneous phase preparation step of preparing a homogeneous phase containing an organic solvent, a polysiloxane precursor, an organic polymer, and water; a mixed solution preparation step of adding carbon nanotubes to the homogeneous phase to prepare a carbon nanotube-containing mixed solution; a condensation hydrophobicization step of condensing part or all of the polysiloxane precursor to form polysiloxane particles and hydrophobicizing the surface of the polysiloxane particles, and a precipitation step of precipitating the organic polymer by a phase separation method to obtain a porous resin, thereby obtaining a precipitate containing the polysiloxane particles and the porous resin; and a drying step of drying the precipitate. Using the above-described method for manufacturing porous sound-absorbing materials, it is possible to obtain porous sound-absorbing materials that have excellent sound absorption properties on the low-frequency side. [Effects of the Invention]
[0017] According to the present invention, a porous sound-absorbing material with excellent sound absorption properties on the low-frequency side can be provided. Furthermore, according to the present invention, it is possible to provide a method for manufacturing a porous sound-absorbing material that has excellent sound absorption properties on the low-frequency side. [Modes for carrying out the invention]
[0018] Embodiments of the present invention will be described in detail below.
[0019] (Porous sound-absorbing material) The porous sound-absorbing material of the present invention comprises a porous resin and carbon nanotubes coating the surface of the porous resin. The porous sound-absorbing material of the present invention has a density of 0.100 g / cm³. 3 More than 0.300g / cm3 The following applies: The porous sound-absorbing material described above exhibits excellent sound absorption on the low-frequency side. This is presumed to be because the air inside the pores of the porous resin of the porous sound-absorbing material having a predetermined density, and the air inside the tubes of the carbon nanotubes, repeatedly compress and expand in accordance with the frequency of the sound that enters the porous sound-absorbing material. The energy loss due to the heat generated during this compression and expansion process, as well as the energy loss due to the vibration of the carbon nanotubes caused by the sound that enters the porous sound-absorbing material, effectively absorbs the low-frequency sound. In other words, the sound that enters the porous sound-absorbing material is effectively converted into thermal energy, vibrational energy, etc. Furthermore, porous sound-absorbing materials like those described above can be very strong. Furthermore, the porous sound-absorbing material of the present invention may also include carbon nanotubes other than those coating the surface of the porous resin, such as carbon nanotubes embedded in the porous resin.
[0020] Since porous sound-absorbing materials can improve sound absorption at low frequencies, it is preferable that they further contain silica xerogel containing polysiloxane particles. Furthermore, when the porous sound-absorbing material contains the above-mentioned silica xerogel, the porous sound-absorbing material can further improve its sound absorption on the low-frequency side. Therefore, it is preferable that the porous resin has a interconnected pore structure, the silica xerogel has a structure in which polysiloxane particles are linked together in a pearl necklace-like manner, and the silica xerogel is present in the interconnected pores of the porous resin.
[0021] The porous sound-absorbing material may optionally contain components other than the porous resin, carbon nanotubes, and silica xerogel described above (hereinafter sometimes referred to as "other components"). Other components include, for example, hydrophobic agents that can be used in the method for producing the porous sound-absorbing material of the present invention, which will be described later.
[0022] <Porous resin> The organic polymer constituting the porous resin contained in the porous sound-absorbing material is not particularly limited, but examples include poly(meth)acrylate alkyl esters such as methyl polyacrylate, ethyl polyacrylate, polymethyl methacrylate, and polyethyl methacrylate; nitrile group-containing polymers such as polyacrylonitrile and polymethacrylonitrile; polylactide; lactide-ε-caprolactone copolymer, etc. These may be used individually or two or more may be combined in any proportion. Among these, the organic polymer is preferably poly(meth)acrylate alkyl ester or nitrile group-containing polymer, and more preferably poly(meth)acrylate alkyl ester, because it is possible to efficiently obtain a porous sound-absorbing material with excellent sound absorption on the low-frequency side. As the poly(meth)acrylate alkyl ester, polymethyl methacrylate is preferred, and as the nitrile group-containing polymer, acrylonitrile is preferred.
[0023] The content of porous resin in the porous sound-absorbing material is preferably 14% by mass or more, more preferably 49% by mass or more, even more preferably 64% by mass or more, preferably 89% by mass or less, and more preferably 74% by mass or less. If the content ratio of porous resin in the porous sound-absorbing material is above the lower limit mentioned above, the porous sound-absorbing material can be effectively made lighter. On the other hand, if the proportion of polysiloxane particles in the porous sound-absorbing material is below the above upper limit, the sound absorption performance of the porous sound-absorbing material on the low-frequency side can be effectively improved.
[0024] <Carbon nanotubes> Carbon nanotubes (hereinafter sometimes referred to as "CNTs") contained in porous sound-absorbing materials are nanocarbon materials having a tubular structure in which graphene sheets are wound into a cylindrical shape, and are broadly classified into single-walled CNTs and multi-walled CNTs based on the number of components in their peripheral walls. In the present specification, "single-layer CNT" refers to a CNT in which the number of tube walls of carbon atoms constituting the CNT is 1 or more and less than 2, and "multi-layer CNT" refers to a CNT in which the number of tube walls of carbon atoms constituting the CNT is 2 or more. Here, the number of tube walls indicates the average number of layers of the CNT, and can be determined from the average value of the number of layers of 100 or more CNTs measured with a transmission electron microscope (TEM) on a dried product of an aqueous CNT dispersion.
[0025] The average diameter (Av) of the CNTs is preferably 0.5 nm or more, more preferably 1 nm or more, preferably 15 nm or less, and more preferably 10 nm or less.
[0026] For the CNTs, it is preferable that the average diameter (Av) and the standard deviation (3σ) of the diameter satisfy the relational expression: 0.60 > "3σ / Av" > 0.20.
[0027] In the present specification, "average diameter (Av)" and "diameter distribution (3σ)" are respectively the average value when the diameters (outer diameters) of 100 randomly selected CNTs are measured with a transmission electron microscope, and the value obtained by multiplying the standard deviation (σ) by 3. The standard deviation in the present specification is the sample standard deviation.
[0028] The BET specific surface area of the CNTs is 600 m 2 / g or more, preferably 800 m 2 / g or more, more preferably 1000 m 2 / g or more, still more preferably. In the present specification, the BET specific surface area of the CNTs is a nitrogen adsorption specific surface area measured using the BET method.
[0029] For the CNTs, the ratio of the G-band peak intensity to the D-band peak intensity (G / D ratio) in the Raman spectrum is preferably 0.5 or more, and preferably 5.0 or less.
[0030] Here, the CNTs having the above-described properties are not particularly limited, and for example, CNTs produced in accordance with a method (super-growth method; see International Publication No. 2006 / 011655) in which raw material compounds and a carrier gas are supplied to a substrate having a catalyst layer for CNT production on its surface, and when CNTs are synthesized by chemical vapor deposition (CVD), a small amount of oxidizing agent (catalyst activator) is present in the system to dramatically improve the catalytic activity of the catalyst layer. In the following, carbon nanotubes obtained by the supergrowth method may be referred to as "SGCNT".
[0031] The mass ratio of CNTs to porous resin in the porous sound-absorbing material (CNT / porous resin) is preferably 0.0010 or higher, more preferably 0.0015 or higher, even more preferably 0.0020 or higher, preferably 0.0100 or lower, more preferably 0.0050 or lower, and even more preferably 0.0030 or lower. If the mass ratio of CNTs to porous resin in the porous sound-absorbing material is within the above range, the sound absorption performance of the porous sound-absorbing material on the low-frequency side can be effectively improved.
[0032] <Silica Xerogel> The silica xerogel that may be included in porous sound-absorbing materials contains polysiloxane particles. The polysiloxane particles included in the silica xerogel can be those formed by condensation of polysiloxane precursors (condensate). Examples of polysiloxane precursors include alkoxysilane compounds such as tetramethoxysilane and tetraethoxysilane; oligomers obtained by partially hydrolyzing alkoxysilane compounds such as tetramethoxysilane and tetraethoxysilane; and organoalkoxysilane compounds such as methyltrimethoxysilane and phenyltrimexysilane. These may be used individually or in combination of two or more in any proportion. Among those listed above, alkoxysilane compounds are preferred as polysiloxane precursors, and tetramethoxysilane is more preferred. That is, polysiloxane particles are preferably composed of condensates of alkoxysilane compounds, and more preferably composed of condensates of tetramethoxysilane.
[0033] In this case, it is preferable that the surface of the polysiloxane particles is hydrophobic. If the surface of the polysiloxane particles is hydrophobic, the polysiloxane particles attract moisture, and when this moisture evaporates, the risk of pore collapse due to surface tension and other factors can be effectively suppressed. As a result, the risk of a decrease in the sound absorption performance of the porous sound-absorbing material can be effectively suppressed. Furthermore, a hydrophobic agent can be used to hydrophobize the surface of polysiloxane particles. Examples of hydrophobic agents include those that can be used in the method for producing the porous sound-absorbing material of the present invention, which will be described later.
[0034] The content of polysiloxane particles in the porous sound-absorbing material is preferably 10% by mass or more, more preferably 25% by mass or more, preferably 85% by mass or less, more preferably 75% by mass or less, and even more preferably 65% by mass or less. If the proportion of polysiloxane particles in the porous sound-absorbing material is above the lower limit mentioned above, the sound absorption performance of the porous sound-absorbing material on the low-frequency side can be effectively improved. On the other hand, if the proportion of polysiloxane particles in the porous sound-absorbing material is below the above upper limit, the porous sound-absorbing material can be effectively made lighter.
[0035] <Other ingredients> The porous sound-absorbing material of the present invention may contain other components such as hydrophobic agents, but the content of these components is preferably 5% by mass or less, preferably 1% by mass or less, more preferably 0.1% by mass or less, and even more preferably 0% by mass. In other words, it is even more preferable that the porous sound-absorbing material does not contain other components.
[0036] <Properties of porous sound-absorbing material> The density of the porous sound-absorbing material is 0.100 g / cm³. 3 The above is required, and the amount is 0.150 g / cm³. 3 Preferably, it is 0.170 g / cm³ or more. 3 It is more preferable that the concentration be 0.300 g / cm³ or higher. 3 The following is required: 0.250 g / cm³ 3 Preferably, it is 0.200 g / cm³. 3 The following is more preferable: If the density of the porous sound-absorbing material is within the above range, the sound-absorbing properties of the porous sound-absorbing material can be effectively improved. The density of the porous sound-absorbing material can be adjusted, for example, by the conditions of each step in the manufacturing method of the porous sound-absorbing material of the present invention, as described later, particularly by the amount and ratio of raw materials used, the conditions for condensing polysiloxane particles, the conditions for precipitating organic polymers, and so on.
[0037] The average pore size A of the porous sound-absorbing material produced by the mercury intrusion method (hereinafter sometimes simply referred to as "average pore size A") is preferably 5.0 μm or more, more preferably 8.0 μm or more, even more preferably 12.0 μm or more, preferably 35.0 μm or less, more preferably 30 μm or less, and even more preferably 25.0 μm or less. If the average pore size A of the porous sound-absorbing material is greater than or equal to the lower limit mentioned above, any silica xerogel can be effectively contained within the voids (pores) of the porous resin. On the other hand, if the average pore size A of the porous sound-absorbing material is below the above upper limit, the sound absorption performance on the low-frequency side of the porous sound-absorbing material can be effectively improved. The average pore size A of the porous sound-absorbing material can be adjusted, for example, by the conditions of each step in the manufacturing method of the porous sound-absorbing material of the present invention, as described later, particularly by the amount and ratio of raw materials used, the conditions for condensing polysiloxane particles, the conditions for precipitating organic polymers, and so on.
[0038] The average pore size B of the porous sound-absorbing material determined by the BJH method (hereinafter sometimes simply referred to as "average pore size B") is preferably 5.0 nm or larger, more preferably 7.0 nm or larger, even more preferably 9.0 nm or larger, preferably 30.0 nm or smaller, more preferably 20.0 nm or smaller, and even more preferably 15.0 nm or smaller. If the average pore size B of the porous sound-absorbing material is within the above range, the sound absorption performance on the low-frequency side of the porous sound-absorbing material can be effectively improved. The average pore size B of the porous sound-absorbing material can be adjusted, for example, by the conditions of each step in the manufacturing method of the porous sound-absorbing material of the present invention, as described later, particularly by the amount and ratio of raw materials used, the conditions for condensing polysiloxane particles, the conditions for precipitating organic polymers, and so on.
[0039] The ratio of average pore diameter B to average pore diameter A (average pore diameter B / average pore diameter A) is preferably 0.10 [nm / μm] or more, more preferably 0.30 [nm / μm] or more, preferably 7.00 [nm / μm] or less, more preferably 5.00 [nm / μm] or less, even more preferably 3.00 [nm / μm] or less, and even more preferably 1.50 [nm / μm] or less. If the ratio of average pore diameter B to average pore diameter A is within the above range, the sound absorption performance of the porous sound-absorbing material on the low-frequency side can be effectively improved.
[0040] The specific surface area A of porous sound-absorbing material obtained by the mercury intrusion method (hereinafter sometimes simply referred to as "specific surface area A") is 50 m². 2 It is preferable that it be 100m or more per gram. 2 It is more preferable that it be 300m or more per gram. 2 It is preferable that it be less than / g, and 200m 2 It is more preferable that it be less than or equal to / g, and 150m 2 It is even more preferable that the amount be less than or equal to / g. If the specific surface area A of the porous sound-absorbing material is above the lower limit mentioned above, the sound absorption performance of the porous sound-absorbing material on the low-frequency side can be effectively improved. On the other hand, if the specific surface area A of the porous sound-absorbing material is less than or equal to the above upper limit, any silica xerogel can be effectively contained within the voids (pores) of the porous resin. The specific surface area A of the porous sound-absorbing material can be adjusted, for example, by the conditions of each step in the manufacturing method of the porous sound-absorbing material of the present invention, as described later, particularly by the amount and ratio of raw materials used, the conditions for condensing polysiloxane particles, the conditions for precipitating organic polymers, and so on. In this specification, the specific surface area A obtained by the mercury intrusion method is the specific surface area measured by the mercury intrusion method, and can be measured according to the method described in the examples of this specification.
[0041] The specific surface area B (hereinafter sometimes simply referred to as "specific surface area B") of porous sound-absorbing material, calculated by the BET method (Brunauer-Emmett-Teller method), is 100m². 2 It is preferable that it be 200m or more per gram. 2 It is more preferable that the amount be 1 / g or more. If the specific surface area B of the porous sound-absorbing material is above the lower limit mentioned above, the sound absorption performance of the porous sound-absorbing material on the low-frequency side can be effectively improved. Note that the specific surface area B is, for example, 500 m². 2 It is less than / g and 400m 2 It is also acceptable to have a value of less than / g, 300m 2 It is also acceptable to use values less than / g. The specific surface area B of the porous sound-absorbing material can be adjusted, for example, by the conditions of each step in the manufacturing method of the porous sound-absorbing material of the present invention, as described later, particularly by the amount and ratio of raw materials used, the conditions for condensing polysiloxane particles, the conditions for precipitating organic polymers, and so on. In this specification, the specific surface area B measured by the BET method is the specific surface area measured by the BET method in the nitrogen adsorption method, and can be measured according to the method described in the examples of this specification.
[0042] The ratio of specific surface area B to specific surface area A (specific surface area B / specific surface area A) is preferably 0.50 or more, more preferably 1.00 or more, even more preferably 2.00 or more, preferably 4.00 or less, and more preferably 2.50 or less. If the ratio of specific surface area B to specific surface area A is within the above range, the sound absorption performance of the porous sound-absorbing material on the low-frequency side can be effectively improved.
[0043] The compressibility of the porous sound-absorbing material is preferably 5% or more, more preferably 8% or more, even more preferably 10% or more, preferably 50% or less, more preferably 25% or less, and even more preferably 15% or less. If the compressibility of the porous sound-absorbing material is above the lower limit mentioned above, the porous sound-absorbing material may exhibit excellent flexibility. On the other hand, if the compressibility of the porous sound-absorbing material is below the above upper limit, the porous sound-absorbing material may have excellent strength. In this specification, the compressibility of the porous sound-absorbing material is the compressibility when pressurized at 0.2 MPa, and can be measured according to the method described in the examples of this specification.
[0044] (Method of manufacturing porous sound-absorbing material) The present invention's method for producing a porous sound-absorbing material (hereinafter sometimes simply referred to as "production method") includes: a homogeneous phase preparation step of preparing a homogeneous phase containing an organic solvent, a polysiloxane precursor, an organic polymer, and water; a mixed solution preparation step of adding carbon nanotubes to the homogeneous phase to prepare a carbon nanotube-containing mixed solution; a precipitate formation step of subjecting the carbon nanotube-containing mixed solution to a condensation hydrophobization step of condensing part or all of the polysiloxane precursor to form polysiloxane particles and hydrophobizing the surface of the polysiloxane particles, and a precipitation step of precipitating the organic polymer by a phase separation method to obtain a porous resin, thereby obtaining a precipitate containing polysiloxane particles and a porous resin; and a drying step of drying the precipitate. With the manufacturing method described above, a porous sound-absorbing material with excellent sound absorption on the low-frequency side can be obtained. Furthermore, with the manufacturing method described above, the porous sound-absorbing material of the present invention described above can be obtained.
[0045] In addition to the homogeneous phase preparation step, mixed solution preparation step, precipitate formation step, and drying step described above, the manufacturing method of the present invention may optionally include a washing step in which the precipitate obtained in the precipitate formation step is washed with a washing solvent, and a solvent replacement step in which the solvent, such as the washing solvent, contained in the precipitate after the washing step is replaced with another solvent (hereinafter sometimes referred to as "replacement solvent").
[0046] <Homogeneous phase preparation process> In the homogeneous phase preparation step, a homogeneous phase is prepared containing an organic solvent, a polysiloxane precursor, an organic polymer, and water. Optionally, components other than the organic solvent, polysiloxane precursor, organic polymer, and water may be added to the homogeneous phase.
[0047] The method for preparing the homogeneous phase is not particularly limited, and examples include (1) a method of preparing the homogeneous phase by mixing each component in any order, (2) a method of preparing an aqueous solution containing an organic solvent first, adding the polysiloxane precursor and the organic polymer to the aqueous solution, and dissolving them together to prepare the homogeneous phase, and (3) a method of preparing an aqueous solution containing an organic solvent first, dissolving one of the polysiloxane precursor and the organic polymer in the aqueous solution, and then dissolving the other to prepare the homogeneous phase. Among these, method (3) is preferred because it allows for efficient acquisition of the homogeneous phase, and it is more preferable to prepare an aqueous solution containing an organic solvent, dissolve the organic polymer in the aqueous solution, and then dissolve the polysiloxane precursor.
[0048] The dissolution temperature of the polysiloxane precursor and organic polymer when preparing the above-mentioned homogeneous phase is not particularly limited as long as it is a temperature at which the homogeneous phase can be maintained, but it is preferably 40°C or higher, more preferably 55°C or higher, preferably 100°C or lower, and more preferably 90°C or lower. If the melting temperature is within the above range, porous sound-absorbing material can be obtained more easily.
[0049] <<Polysiloxane precursor>> The polysiloxane precursor is not particularly limited as long as it forms polysiloxane particles and yields a homogeneous phase, but examples include alkoxysilane compounds such as tetramethoxysilane and tetraethoxysilane; oligomers obtained by partially hydrolyzing alkoxysilane compounds such as tetramethoxysilane and tetraethoxysilane; and organoalkoxysilane compounds such as methyltrimethoxysilane and phenyltrimexysilane. These may be used individually or in combination of two or more in any proportion. Among these, alkoxysilane compounds are preferred as the polysiloxane precursor because they allow for easier acquisition of porous sound-absorbing materials, and tetramethoxysilane is more preferred.
[0050] The content of the polysiloxane precursor in the homogeneous phase is preferably 4.0% by mass or more, more preferably 8.0% by mass or more, preferably 40.0% by mass or less, more preferably 30.0% by mass or less, and even more preferably 25.0% by mass or less. If the content of the polysiloxane precursor in the homogeneous phase is above the lower limit mentioned above, the condensation of the polysiloxane precursor can be carried out efficiently in the condensation process. Furthermore, the sound absorption properties on the low-frequency side of the resulting porous sound-absorbing material can be effectively improved. On the other hand, if the proportion of polysiloxane precursor in the homogeneous phase is below the above upper limit, manufacturing costs can be effectively reduced.
[0051] <<Organic Polymers>> The organic polymer is not particularly limited as long as it forms a porous resin and yields a homogeneous phase, but examples include poly(meth)acrylate alkyl esters such as methyl polyacrylate, ethyl polyacrylate, polymethyl methacrylate, and polyethyl methacrylate; nitrile group-containing polymers such as polyacrylonitrile and polymethacrylonitrile; polylactide; and lactide-ε-caprolactone copolymer. These may be used individually or in any combination of two or more in any proportion. Among these, the organic polymer is preferably a poly(meth)acrylate alkyl ester or a nitrile group-containing polymer, and more preferably a poly(meth)acrylate alkyl ester. Polymethyl methacrylate is preferred as the poly(meth)acrylate alkyl ester, and acrylonitrile is preferred as the nitrile group-containing polymer.
[0052] The content of the organic polymer in the homogeneous phase is preferably 1.0% by mass or more, more preferably 4.0% by mass or more, particularly preferably 6.0% by mass or more, preferably 30.0% by mass or less, more preferably 20.0% by mass or less, and even more preferably 12.0% by mass or less. If the content of the organic polymer in the homogeneous phase is above the lower limit mentioned above, the organic polymer can be efficiently precipitated in the precipitation process. On the other hand, if the proportion of organic polymer in the homogeneous phase is below the above upper limit, the organic polymer becomes more easily soluble in organic solvents, and the manufacturing process can be made more efficient. In addition, the sound absorption properties on the low-frequency side of the resulting porous sound-absorbing material can be effectively improved.
[0053] Here, the mass ratio of the organic polymer to the polysiloxane precursor in the homogeneous phase (organic polymer / polysiloxane precursor) is preferably 0.10 or higher, more preferably 0.20 or higher, even more preferably 0.40 or higher, preferably 2.00 or lower, and more preferably 1.20 or lower. If the mass ratio of the organic polymer to the polysiloxane precursor is above the lower limit mentioned above, the sound absorption properties on the low-frequency side of the resulting porous sound-absorbing material can be effectively improved. On the other hand, if the mass ratio of the organic polymer to the polysiloxane precursor is below the above upper limit, the strength of the porous sound-absorbing material can be effectively improved.
[0054] <<Organic solvent>> The organic solvent is not particularly limited as long as it can produce a homogeneous phase, but examples include alcohols such as methanol and ethanol; sulfur-containing solvents such as dimethyl sulfoxide and sulfolane; ketones such as acetone and methyl ethyl ketone; and tetrahydrofuran. These may be used individually or in combination of two or more in any proportion. The organic solvent is preferably an alcohol or a sulfur-containing solvent. Ethanol is preferred as the alcohol, and dimethyl sulfoxide is preferred as the sulfur-containing solvent.
[0055] The content of the organic solvent in the homogeneous phase is preferably 20.0% by mass or more, more preferably 40.0% by mass or more, even more preferably 60.0% by mass or more, preferably 95.0% by mass or less, and more preferably 85.0% by mass or less. If the proportion of organic solvent in the homogeneous phase is above the lower limit mentioned above, the organic polymer can be efficiently dissolved. On the other hand, if the proportion of organic solvent in the homogeneous phase is below the above upper limit, the precipitation of the organic polymer in the precipitation process will be accelerated, effectively improving productivity. Furthermore, the sound absorption properties on the low-frequency side of the resulting porous sound-absorbing material can be effectively improved.
[0056] <<Solid content concentration of homogeneous phase>> The solid content concentration of the homogeneous phase is preferably 5.0% by mass or more, more preferably 8.0% by mass or more, preferably 60.0% by mass or less, and more preferably 40.0% by mass or less.
[0057] <Mixed liquid preparation process> In the mixture preparation step, carbon nanotubes are added to a homogeneous phase to prepare a carbon nanotube-containing mixture (hereinafter sometimes referred to as "CNT-containing mixture"). Here, the carbon nanotubes added to the homogeneous phase can be those described in the "carbon nanotubes" section of the porous sound-absorbing material of the present invention described above.
[0058] CNTs may be added to the homogeneous phase in the form of a CNT dispersion. The CNT dispersion can be prepared by conventionally known methods. The CNT content in the CNT dispersion that can be added to the homogeneous phase is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, even more preferably 0.015% by mass or more, preferably 0.5% by mass or less, more preferably 0.1% by mass or less, and even more preferably 0.03% by mass or less.
[0059] The CNT content in the CNT-containing mixture is preferably 0.003% by mass or more, more preferably 0.005% by mass or more, even more preferably 0.008% by mass or more, preferably 0.050% by mass or less, more preferably 0.025% by mass or less, and even more preferably 0.015% by mass or less. If the proportion of CNTs in the CNT-containing mixture is within the above range, the sound absorption properties on the low-frequency side of the resulting porous sound-absorbing material can be effectively improved.
[0060] The mass ratio of CNTs to organic polymers in the CNT-containing mixture (CNT / organic polymer) is preferably 0.0010 or higher, more preferably 0.0015 or higher, even more preferably 0.0020 or higher, preferably 0.0100 or lower, more preferably 0.0050 or lower, and even more preferably 0.0030 or lower. If the mass ratio of CNTs to organic polymers in the CNT-containing mixture is within the above range, the sound absorption properties on the low-frequency side of the resulting porous sound-absorbing material can be effectively improved.
[0061] <Precipitate formation process> In the precipitate formation process, the carbon nanotube-containing mixture prepared in the mixture preparation process is used. A condensation hydrophobicization step involves condensing part or all of a polysiloxane precursor to form polysiloxane particles and hydrophobicizing the surface of the polysiloxane particles, and Precipitation process to obtain porous resin by precipitating organic polymers using a phase separation method. By applying this method, a precipitate containing polysiloxane particles and porous resin is obtained. The precipitate obtained by the above precipitate formation process has the desired porous state internally and maintains that porous state. Therefore, it can be dried without supercritical drying in the subsequent drying process.
[0062] In this context, the order in which the CNT-containing mixture prepared in the mixture preparation step is subjected to the condensation hydrophobicization step and the precipitation step in the precipitate formation step is not particularly limited. In the precipitate formation process, the condensation hydrophobication step may be performed before the precipitation step, the precipitation step may be performed before the condensation hydrophobication step, or the condensation hydrophobication step and the precipitation step may be performed simultaneously. However, it is preferable to perform the condensation hydrophobication step before the precipitation step because it is easier to obtain porous sound-absorbing material.
[0063] In the following, the precipitate formation process will be explained using a precipitate formation process in which a condensation hydrophobicization process is performed followed by a precipitation process as an example; however, the precipitate formation process in the manufacturing method of the present invention is not limited to this.
[0064] <<Condensation Hydrophobicization Process>> In the condensation hydrophobicization process, part or all of the polysiloxane precursor is condensed to form polysiloxane particles (condensation process), and the surface of the polysiloxane particles is made hydrophobic (hydrophobicization process). The condensation hydrophobicization step may optionally include a gel formation step between the condensation step and the hydrophobicization step, in which the solution after the condensation step is left for a predetermined time to obtain a wet gel, and a crushing step in which the gel obtained in the gel formation step is crushed.
[0065] [Condensation step] In the condensation process, some or all of the polysiloxane precursor is condensed to form polysiloxane particles.
[0066] The condensation of polysiloxane precursors is not particularly limited as long as polysiloxane particles can be obtained, but it can be carried out by adding a catalyst to a CNT-containing mixture. Examples of catalysts include base catalysts such as aqueous ammonia, urea, and amines; and acid catalysts such as hydrochloric acid, acetic acid, and oxalic acid. These may be used individually or in any combination of two or more in any proportion. Among these, base catalysts are preferred, and aqueous ammonia is more preferred.
[0067] The amount of catalyst added to the CNT-containing mixture is preferably 0.05 mmol or more, more preferably 0.01 mmol or more, more preferably 0.3 mmol or less, and more preferably 0.2 mmol or less, per mole of polysiloxane precursor.
[0068] The condensation time of the polysiloxane precursor is preferably 1 minute or more, more preferably 5 minutes or more, preferably 20 minutes or less, and more preferably 15 minutes or less. If the condensation time of the polysiloxane precursor is above the lower limit mentioned above, the amount of unreacted polysiloxane precursor can be effectively suppressed. On the other hand, if the condensation time of the polysiloxane precursor is below the above upper limit, the productivity of porous sound-absorbing materials can be effectively improved. The condensation time mentioned above refers to the time from when the catalyst is added to the CNT-containing mixture until the formation of the gel, described later, begins, or until the hydrophobicization process, described later, begins.
[0069] The condensation temperature of polysiloxane precursors is typically between 23°C and 80°C.
[0070] [Gel formation process] In any gel formation step, the solution after the condensation step is left to stand for a predetermined time to obtain a wet gel. By including a gel formation step in the condensation and hydrophobicization process, the polysiloxane precursor can be sufficiently condensed to efficiently obtain polysiloxane particles.
[0071] The standing time in the gel formation process is preferably 0.1 hours or more, more preferably 0.5 hours or more, preferably 24 hours or less, and more preferably 12 hours or less. If the standing time during the gel formation process is above the lower limit mentioned above, the amount of unreacted polysiloxane precursor can be effectively suppressed. On the other hand, if the standing time in the gel formation process is below the above upper limit, the productivity of porous sound-absorbing materials can be effectively improved. The above-mentioned standing time refers to the time from when the formation of the gel body begins until the start of any of the disintegration steps described later, or until the start of the hydrophobicization step described later.
[0072] The standing temperature during the gel formation process is typically between 23°C and 80°C.
[0073] [Crushing process] In any disintegration step, the gel obtained in the gel formation step is disintegrated. By including a crushing step in the condensation hydrophobicization process, the hydrophobicization process can be carried out more efficiently. The disintegration of the gel is not particularly limited and may be done automatically using a stirrer or by hand using a rod or the like.
[0074] In the crushing step, the viscosity may be adjusted by adding the aforementioned organic solvent or aqueous solution containing an organic solvent to the gel. This allows the gel to be crushed efficiently. The amount of organic solvent or aqueous solution containing an organic solvent used can be adjusted as appropriate to the desired viscosity.
[0075] In the crushing process, the gel may be heated to suppress the precipitation of organic polymers. This allows for efficient crushing of the gel. The heating temperature is not particularly limited as long as it can suppress the precipitation of the organic polymer, but it is preferably 40°C or higher, preferably 50°C or higher, preferably 70°C or lower, and more preferably 65°C or lower.
[0076] [Hydrophobicization process] In the hydrophobicization process, the surface of the polysiloxane particles is made hydrophobic. By making the surface of the polysiloxane particles hydrophobic, the risk of pore collapse due to surface tension and other factors when moisture attracted to the polysiloxane particles evaporates during the drying process described later can be effectively suppressed. As a result, the risk of a decrease in the sound absorption properties of the resulting porous sound-absorbing material can be effectively suppressed. In addition, hydrophobic agents are typically used to hydrophobize the surface of polysiloxane particles.
[0077] Alkoxyalkylsilanes can be used as hydrophobic agents in the hydrophobication process. Examples of alkoxyalkylsilanes include monoalkoxytrialkylsilanes, dialoxydialkylsilanes, and trialkoxymonoalkylsilanes. Among these, trialkoxymonoalkylsilanes are preferred. Examples of trialkoxy monoalkylsilanes include trimethoxymethylsilane, trimethoxypropylsilane, trimethoxyhexylsilane, trimethoxydecylsilane, triethoxymethylsilane, and triethoxypropylsilane. Among these, trimethoxymethylsilane is preferred. The items listed above may be used individually or in any combination of two or more items in any proportion.
[0078] The mass ratio of the hydrophobic agent to the polysiloxane precursor used in the homogeneous phase preparation step (hydrophobic agent / polysiloxane precursor) is preferably 0.1 or higher, more preferably 0.3 or higher, even more preferably 0.5 or higher, preferably 5.0 or lower, more preferably 2.0 or lower, and even more preferably 1.0 or lower. If the mass ratio of the hydrophobic agent to the polysiloxane precursor is above the lower limit mentioned above, the sound absorption properties on the low-frequency side of the resulting porous sound-absorbing material can be effectively improved.
[0079] <<Precipitation process>> In the precipitation process, an organic polymer is precipitated by a phase separation method to obtain a porous resin. If the precipitate formation step involves a condensation hydrophobicization step followed by a precipitation step, the precipitation step can yield a precipitate containing polysiloxane particles and porous resin. This precipitate is typically in a wet state.
[0080] In the precipitation process, the phase separation method is not particularly limited as long as it allows for the precipitation of the organic polymer to obtain a porous resin. However, a thermally induced phase separation method is preferred, i.e., a method in which a solution or gel containing the organic polymer is cooled to precipitate the porous resin, as this makes it easier to obtain a porous sound-absorbing material.
[0081] When using the thermally induced phase separation method in the precipitation process, the cooling temperature is not particularly limited as long as it is below the crystallization temperature (crystalline polymer) or glass transition temperature (amorphous polymer) of the organic polymer, as it is the cooling temperature at which the structure of the porous resin solidifies. However, it is preferably -40°C or higher, more preferably -30°C or higher, preferably 0°C or lower, and even more preferably -10°C or lower. If the cooling temperature is above the lower limit mentioned above, the freezing of organic solvents and water can be suppressed, effectively improving the productivity of porous sound-absorbing materials. On the other hand, if the cooling temperature is below the above upper limit, the porous resin can be efficiently precipitated.
[0082] When using the thermally induced phase separation method in the precipitation process, the cooling time is usually between 5 minutes and 3 hours.
[0083] <Washing process> In any washing step, the precipitate obtained in the precipitate formation step is washed with a washing solvent. This effectively removes unreacted polysiloxane precursors, hydrophobic agents, and other impurities.
[0084] As a cleaning solvent, a solvent that is a poor solvent for porous resins and a good solvent for water can be used. For example, the solvents listed in the "organic solvents" section above can be used.
[0085] The temperature of the washing solvent used when washing precipitates is typically between -40°C and 0°C.
[0086] <Solvent replacement process> In the optional solvent replacement step, the solvent, such as the washing solvent, contained in the precipitate after the washing step is replaced with a replacement solvent. This allows for efficient drying of the precipitate in the drying step described later. Furthermore, it effectively suppresses damage to the precipitate, such as cracking.
[0087] As the substitution solvent, a solvent that is a poor solvent for porous resins and has a lower surface tension than the washing solvent can be used. For example, alkanes such as n-hexane and n-heptane can be used. Among these, n-heptane is preferred.
[0088] <Drying process> In the drying step, the precipitate obtained in the precipitate formation step, optional washing step, or optional solvent substitution step is dried. In the manufacturing method of the present invention, the interior of the precipitate is in the desired porous state, and it is possible to dry it while maintaining the porous state, so drying can be done without supercritical drying. For this reason, supercritical drying is not usually performed in the drying step of the manufacturing method of the present invention.
[0089] The drying temperature of the precipitate is not particularly limited as long as the solvent contained in the precipitate (organic solvent, water, washing solvent, substitution solvent, etc.) can be removed, but it is usually between 20°C and 40°C.
[0090] The drying time for the precipitate is not particularly limited as long as the solvent contained in the precipitate can be removed, but it is usually between 2 and 24 hours. [Examples]
[0091] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples. In the examples and comparative examples, the polysiloxane particle content, density, average pore size A and specific surface area A by mercury intrusion method, specific surface area B by BET method, average pore size B by BJT method, compressibility, and sound absorption coefficient on the low-frequency side were measured using the following procedure.
[0092] <Polysiloxane particle content> The polysiloxane particle content of the porous sound-absorbing materials obtained in the examples and comparative examples was measured using a differential scanning calorimetry analyzer (STA7200, manufactured by Hitachi High-Tech Science). Specifically, samples cut from porous sound-absorbing material were placed in an aluminum container designed for the apparatus, and heated to 500°C under conditions of a nitrogen gas flow rate of 20 mL / min and a temperature of 20°C / min to obtain a TG curve. Using the analysis software provided with the apparatus, the residual weight percentage at 500°C was calculated, and this calculated value was taken as the content ratio of polysiloxane particles.
[0093] <density> The mass of the porous sound-absorbing material obtained in the examples and comparative examples was measured using an electronic balance, and the density of the porous sound-absorbing material (m³) was obtained by dividing the mass by the volume of the porous sound-absorbing material. 2 We calculated / g).
[0094] <Average pore size A and specific surface area A by mercury intrusion method> Using a mercury porosimeter (AutoPore V9620 manufactured by Micromeritics Instrument Corporation), the average pore diameter A of the porous sound-absorbing material was determined by a mercury intrusion method. In the measurement by the mercury intrusion method using a mercury porosimeter, the pore diameter is determined by modeling the pores as cylindrical, and is calculated by the Washburn equation (-4σcosθ=PD, where σ represents the surface tension of mercury (N / m), θ represents the contact angle (deg), D represents the pore diameter (m), and P represents the pressure (Pa)). Specifically, the porous sound-absorbing materials obtained in Examples and Comparative Examples were vacuum-dried at 80°C for 8 hours, the measurement was performed under the following conditions, and the pore diameter at which the cumulative pore volume reached 50% of the total pore volume was defined as the average pore diameter A of the porous sound-absorbing material. In addition, the specific surface area A of the porous sound-absorbing material was determined from the obtained value of the cumulative pore volume. Measurement range: φ0.0036 μm to 200 μm Mercury contact angle: 140° Mercury surface tension: 480 dynes / cm (0.480 N / m)
[0095] <Specific Surface Area B by BET Method> Using a specific surface area measurement device (BELSORP-miniII manufactured by MicrotracBEL Corp.), nitrogen gas was adsorbed onto the porous sound-absorbing materials obtained in Examples and Comparative Examples, and the specific surface area B of the porous sound-absorbing material was measured by the BET method in the nitrogen adsorption method.
[0096] <Average Pore Diameter B by BJH Method> Using a specific surface area measurement device (BELSORP-miniII manufactured by MicrotracBEL Corp.), nitrogen gas was adsorbed onto the porous sound-absorbing materials obtained in Examples and Comparative Examples, and the average pore diameter B of the porous sound-absorbing material was measured by the BJH method in the nitrogen adsorption method. Specifically, nitrogen gas was adsorbed onto the porous sound-absorbing materials obtained in Examples and Comparative Examples to measure a nitrogen adsorption isotherm, a BJH plot was calculated from the nitrogen adsorption isotherm, then the pore diameter peak on the adsorption side was determined from the obtained BJH plot, and the pore diameter peak was defined as the average pore diameter B of the porous sound-absorbing material.
[0097] <Compression Ratio> The compressibility of the porous sound-absorbing materials obtained in Examples and Comparative Examples was measured using a compression tester (manufactured by Instron, Model 68SC-1). Specifically, the porous sound-absorbing material placed on a pedestal was pressurized at 0.2 MPa from above, and the compression degree of the porous sound-absorbing material was calculated as the compressibility using the following formula (1). Here, in formula (1), T0 means the thickness of the sample (porous sound-absorbing material) before pressurization, and T0.2 means the thickness of the sample (porous sound-absorbing material) when a pressure of 0.2 MPa is applied. When the porous sound-absorbing material cannot withstand pressurization of 0.2 MPa, that is, when it is broken by pressurization of 0.2 MPa, the compressibility of the porous sound-absorbing material can be a value close to 100%. Compressibility (%) = 100 × [1 - (T0.2 / T0)] ··· (1)
[0098] <Sound Absorption Rate on Low Frequency Side> Using the porous sound-absorbing materials obtained in Examples and Comparative Examples, the sound absorption rate with respect to frequency was measured in accordance with ASTM E1050 using a normal incidence sound absorption rate measuring apparatus (manufactured by Nihon Onkyo Engineering Co., Ltd., apparatus name: winZacMTX-15). From the obtained graph of sound absorption rate and frequency, the sound absorption rates of sounds at 3000 Hz and 6000 Hz were confirmed.
[0099] (Example 1) <Preparation of CNT Dispersion Liquid> In an 80 vol% ethanol aqueous solution as a dispersion medium, single-walled CNTs as fibrous carbon nanostructures (manufactured by Zeon Nano Technology Co., Ltd., product name "ZEONANO (registered trademark) SG101", SGCNT, average diameter: 3.5 nm, average length: 400 μm, BET specific surface area: 1050 m 2 / g), and S-LEC BL-S (manufactured by Sekisui Chemical) as a dispersant were added so that the concentration would be 1.0 mass% (5 times the mass of CNTs), followed by stirring with a magnetic stirrer for 1 hour to obtain a crude dispersion liquid. Next, the crude dispersion was filled into a multi-stage step-down high-pressure homogenizer (BERYU SYSTEM PRO, manufactured by Miyu Co., Ltd.) which has a multi-stage pressure control device (multi-stage step-down converter) connected to a high-pressure dispersion processing unit (jet mill) having a 170 μm diameter tubular channel. At a temperature of 25°C, a pressure of 100 MPa was intermittently and instantaneously applied to the crude dispersion and sent into the tubular channel. This constituted one cycle, and this was repeated for three cycles. Furthermore, the previous capillary channel was replaced with a capillary channel with a diameter of 90 μm, and the same dispersion treatment was performed for one cycle. This was repeated 12 times. Then, the CNT dispersion was prepared by diluting with an 80 volume% ethanol aqueous solution until the CNT concentration reached 0.02 mass%.
[0100] <Homogeneous phase preparation process> 0.625 g of polymethyl methacrylate (PMMA) as an organic polymer was dissolved in 6 mL of 80 vol% aqueous ethanol solution at 60°C. Then, 0.64 g of tetramethoxysilane (manufactured by Tokyo Ohka Kogyo Co., Ltd.) as a polysiloxane precursor was added to the resulting solution to obtain a homogeneous solution (homogeneous phase).
[0101] <Mixed liquid preparation process> To the homogeneous solution obtained in the homogeneous phase preparation step, 7 g of the prepared CNT dispersion was added to prepare a CNT-containing mixture.
[0102] <Precipitate formation process> To the CNT-containing mixture obtained in the mixture preparation step, 0.354 mL of 1.73 M aqueous ammonia (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (equivalent to 6.1 mmol of ammonia) was added little by little, and the mixture was left to stand for 10 minutes after the addition was completed (condensation step). Next, 0.40 g of trimethoxymethylsilane (manufactured by Tokyo Ohka Kogyo Co., Ltd.) was added to the standing solution as a hydrophobic agent (hydrophobicization step). Then, the solution after the addition of the hydrophobic agent was cooled at -20°C for 15 minutes to obtain a wet precipitate (precipitation step).
[0103] <Washing process> The precipitate obtained in the precipitate formation process was washed with ethanol at -20°C.
[0104] <Solvent replacement process> Using n-heptane at -20°C, the solvent of the precipitate after the washing step was replaced from ethanol to heptane.
[0105] <Drying process> The precipitate after the solvent replacement step was dried at room temperature to obtain a porous sound-absorbing material. Using the obtained porous sound-absorbing material, the polysiloxane particle content, density, average pore size A and specific surface area A by mercury intrusion method, specific surface area B by BET method, average pore size B by BJT method, compressibility, and sound absorption coefficient at low frequencies were measured. The results are shown in Table 1. Furthermore, a scanning electron microscope (SEM) examination of the obtained porous sound-absorbing material revealed that carbon nanotubes were covering the surface of the porous resin. Furthermore, when the obtained porous sound-absorbing material was examined using a scanning electron microscope (SEM), it was found that the porous resin had a structure of interconnected pores, and the silica xerogel had a structure in which polysiloxane particles were linked together in a pearl necklace-like manner, with the silica xerogel present within the interconnected pores of the porous resin.
[0106] (Example 2) In preparing the CNT dispersion, the CNTs were diluted to a concentration of 0.04% by mass to prepare the dispersion, and this dispersion was used in the mixture preparation step. Except for these differences, various operations and measurements were carried out in the same manner as in Example 1. The results are shown in Table 1. Furthermore, a scanning electron microscope (SEM) examination of the obtained porous sound-absorbing material revealed that carbon nanotubes were covering the surface of the porous resin. Furthermore, when the obtained porous sound-absorbing material was examined using a scanning electron microscope (SEM), it was found that the porous resin had a structure of interconnected pores, and the silica xerogel had a structure in which polysiloxane particles were linked together in a pearl necklace-like manner, with the silica xerogel present within the interconnected pores of the porous resin.
[0107] (Example 3) In preparing the CNT dispersion, the CNTs were diluted until the concentration was 0.01% by mass to prepare the dispersion, and this dispersion was used in the mixture preparation step. Except for these differences, various operations and measurements were carried out in the same manner as in Example 1. The results are shown in Table 1. Furthermore, a scanning electron microscope (SEM) examination of the obtained porous sound-absorbing material revealed that carbon nanotubes were covering the surface of the porous resin. Furthermore, when the obtained porous sound-absorbing material was examined using a scanning electron microscope (SEM), it was found that the porous resin had a structure of interconnected pores, and the silica xerogel had a structure in which polysiloxane particles were linked together in a pearl necklace-like manner, with the silica xerogel present within the interconnected pores of the porous resin.
[0108] (Comparative Example 1) Except for not adding the CNT dispersion to the homogeneous solution during the mixture preparation step, i.e., the homogeneous solution was subjected directly to the precipitate formation step, various operations and measurements were carried out in the same manner as in Example 1. The results are shown in Table 1.
[0109] Note that in Table 1, "PMMA" stands for polymethyl methacrylate. "TMA" stands for tetramethoxysilane. "CNT / Organic Polymer (Mass Ratio)" indicates the mass ratio of CNTs to organic polymer.
[0110] [Table 1]
[0111] As is clear from Table 1, the porous sound-absorbing materials of Examples 1-3 exhibit high sound absorption coefficients at low frequencies (3000Hz, 6000Hz), indicating superior sound absorption in the low-frequency range. Furthermore, the porous sound-absorbing material of Example 1 exhibits even greater sound absorption in the lower-frequency range, as it has a high sound absorption coefficient at 3000Hz. [Industrial applicability]
[0112] According to the present invention, a porous sound-absorbing material with excellent sound absorption properties on the low-frequency side can be provided. Furthermore, according to the present invention, it is possible to provide a method for manufacturing a porous sound-absorbing material that has excellent sound absorption properties on the low-frequency side.
Claims
1. The material comprises a porous resin and carbon nanotubes covering the surface of the porous resin. The density is 0.100 g / cm³. 3 0.300g / cm or more 3 The following are porous sound-absorbing materials.
2. The porous sound-absorbing material according to claim 1, wherein the average pore size A obtained by the mercury intrusion method is 5.0 μm or more and 35.0 μm or less.
3. The porous sound-absorbing material according to claim 1, wherein the average pore size B determined by the BJH method is 5.0 nm or more and 30.0 nm or less.
4. The porous sound-absorbing material according to claim 1, further comprising a silica xerogel containing the polysiloxane particles.
5. The porous resin has a structure of interconnected holes, The silica xerogel has a structure in which the polysiloxane particles are linked together in a pearl necklace-like manner. The porous sound-absorbing material according to claim 4, wherein the silica xerogel is present in the interconnected pores of the porous resin.
6. The porous sound-absorbing material according to claim 4 or 5, wherein the content ratio of the polysiloxane particles in the porous sound-absorbing material is 10% by mass or more and 85% by mass or less.
7. A homogeneous phase preparation step involves preparing a homogeneous phase containing an organic solvent, a polysiloxane precursor, an organic polymer, and water. A mixture preparation step involves adding carbon nanotubes to the homogeneous phase to prepare a carbon nanotube-containing mixture, The carbon nanotube-containing mixture is A condensation hydrophobicization step in which part or all of the polysiloxane precursor is condensed to form polysiloxane particles, and the surface of the polysiloxane particles is made hydrophobic, and Precipitation step to obtain a porous resin by precipitating the organic polymer by a phase separation method. A precipitate formation step is performed to obtain a precipitate containing the polysiloxane particles and the porous resin, A drying step for drying the precipitate, A method for manufacturing porous sound-absorbing material, including
Citation Information
Patent Citations
Sound absorption material and using method of porous material to sound absorption material
JP2021179459A